High-toughness nickel-based multi-principal-element alloy and preparation method thereof
High strength nickel-based multi-main alloys were prepared by preparing Ni: 53-55%, Cr: 18-20%, Co: 15-17%, Al: 5-6%, V: 4-5%, combined with vacuum arc furnace Smelting and heat treatment technology solves the problem of mismatch between strength and toughness in high-stress environments in traditional nickel-based alloys, achieving coordination between high strength and high toughness, and significantly improving mechanical properties.
Patent Information
- Application Number
- CN202411322207.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-10
AI Technical Summary
Traditional nickel-based alloys have limitations in both high strength and high toughness, and are difficult to effectively apply in high stress environments. Moreover, the mechanical properties of nickel-based multi-main alloys are less studied, and the nickel-based multi-main alloys are selected. Insufficient system.
Using high-strength nickel-based multi-main alloys with Ni: 53-55%, Cr: 18-20%, Co: 15-17%, Al: 5-6%, V: 4-5%, melted by vacuum arc furnace , homogenized annealing, cold rolling deformation and aging heat treatment to prepare alloys with good strength and toughness.
The matching of high strength and high toughness was achieved. The yield strength of the alloy after aging treatment was 925.5MPa, the ultimate tensile strength was 1268.6MPa, the elongation was 24.1%, the microstructure was a single-phase face-centered cubic structure, and the grain size was fine. Excellent mechanical properties.
Smart Images

Figure CN119287218A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of novel metal materials and preparation thereof, and in particular relates to a high-strength and toughness nickel-based multi-principal-element alloy and a preparation method thereof. Background Art
[0002] The field of metal materials occupies a vital position in modern industry, especially in high-demand application scenarios such as aerospace, automobile manufacturing, energy and chemical industry. With the continuous development of technology, the performance requirements for metal materials are also constantly increasing, especially the requirements for strength and toughness are becoming increasingly stringent. As a new type of alloy material, multi-principal alloy has attracted much attention in recent years due to its excellent mechanical properties and broad application prospects.
[0003] In practical applications, the mechanical properties of materials require not only high strength, but also sufficient toughness to resist fracture and damage under complex stress environments. Traditional materials often find it difficult to perform well in both aspects at the same time. High-strength materials are usually brittle, while high-toughness materials are insufficiently strong. This mismatch in mechanical properties limits the application of materials in high-stress environments. Although traditional nickel-based alloys excel in high-temperature strength and oxidation resistance, they have certain limitations in having both high strength and high toughness. The unique microstructure of multi-principal component alloys enables them to exhibit unique advantages in performance, such as high strength, high toughness, high oxidation resistance and excellent corrosion resistance. At present, there is little research on the strengthening and toughening of the mechanical properties of nickel-based multi-principal component alloys, and there are insufficient nickel-based multi-principal component alloy systems to choose from.
[0004] In view of the above reasons, research and development of nickel-based multi-principal component alloys with good strength-toughness matching is of great significance to the development and application of nickel-based multi-principal component alloys. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes a high-strength and toughness nickel-based multi-principal component alloy and a preparation method thereof. The preparation method and heat treatment method are simple and convenient, and the alloy has a good match between strength and toughness.
[0006] To achieve the above objectives, the present invention provides a high-strength and tough nickel-based multi-principal component alloy, wherein the constituent elements of the high-strength and tough nickel-based multi-principal component alloy are Ni: 53-55%, Cr: 18-20%, Co: 15-17%, Al: 5-6%, and V: 4-5% by mass percentage.
[0007] Furthermore, the constituent elements of the high-strength and toughness nickel-based multi-principal alloy are Ni 54.51%, Cr 19.32%, Co 16.44%, Al 5.01%, and V 4.73% in mass percentage.
[0008] The present invention also provides a method for preparing a high-strength and tough nickel-based multi-principal-element alloy, the preparation method comprising the following steps:
[0009] (1) cleaning and proportioning the raw materials according to the mass percentage of the constituent elements of the high-strength and toughness nickel-based multi-principal alloy;
[0010] (2) placing the raw materials obtained in step (1) in a vacuum arc furnace for melting, and obtaining a multi-principal alloy block by suction casting;
[0011] (3) The multi-principal component alloy block described in step (2) is subjected to homogenization annealing, rolling deformation and subsequent heat treatment to obtain the high-strength and toughness nickel-based multi-principal component alloy.
[0012] Furthermore, in step (1), the raw material cleaning is to place Ni, Cr, Co, Al, V metal particles with a purity of 99.99wt.% in a clean beaker, and use anhydrous ethanol to ultrasonically clean and dry them.
[0013] Furthermore, in step (2), the specific steps of the vacuum arc furnace smelting are:
[0014] (2.1) The raw materials prepared in step (1) are placed in a copper crucible of a vacuum arc furnace in order of melting point from low to high, the furnace door is closed, and a mechanical pump and a molecular pump are used to perform vacuum treatment in sequence, so that the pressure in the furnace reaches 1×10 -4 Pa, then high-purity argon is introduced into the furnace, and the above steps are repeated three times to exhaust all the oxygen in the furnace and obtain a clean vacuum atmosphere;
[0015] (2.2) After the treatment in step (2.1), high-purity argon gas is introduced into the furnace so that the pressure in the furnace chamber is -0.05 MPa;
[0016] (2.3) In the atmosphere treated in step (2.2), the cleanliness of the furnace is further checked by first melting pure titanium balls and observing the color change of their surface. During the smelting process, multiple main component alloys are smelted by controlling the current at 40-200A. After each smelting, the alloy is turned over and the smelting is repeated for more than 8 times, and electromagnetic stirring is used to further promote the uniformity of the alloy composition.
[0017] Furthermore, in step (2), the suction casting is to use a water-cooled copper mold to suction cast the product smelted in the vacuum arc furnace to obtain a multi-principal alloy block with a size of 10 mm×10 mm×80 mm.
[0018] Furthermore, in step (3), the treatment temperature during the homogenization annealing treatment is 1200° C., and the insulation time is 24 hours. After the insulation is completed, the multi-principal component alloy block is cooled to room temperature by water cooling.
[0019] Furthermore, in step (3), the rolling deformation is performed by multiple cold rolling passes, with the reduction amount of each deformation not exceeding 0.5 mm, and the final rolling deformation amount being 80%.
[0020] Furthermore, in step (3), the subsequent heat treatment includes recrystallization annealing and aging heat treatment; the temperature of the recrystallization annealing is 1100°C, the holding time is 10 minutes, and after the holding is completed, the product is water-cooled to room temperature; the temperature of the aging heat treatment is 700°C, the holding time is 1-12 hours, and after the holding is completed, the product is water-cooled to room temperature.
[0021] Furthermore, the holding time during the aging heat treatment process is 12 hours.
[0022] Compared with the prior art, the present invention has the following advantages and technical effects:
[0023] The present invention relates to a high-strength and tough nickel-based multi-principal alloy, which has a simple preparation method and a simple heat treatment method, and has good strength and toughness matching. After aging at 700°C for 12 hours, the mechanical properties are optimal. Specifically, the Ni prepared by the present invention 54.51 Cr 19.32 Co 16.44 Al 5.01 V 4.73 (mass percentage) multi-principal alloy, the microstructure after cold rolling deformation and recrystallization treatment is a single-phase face-centered cubic structure, the average grain size is 62.45μm, after aging treatment at 700℃, L12 phase precipitates in the face-centered cubic matrix, and the average grain size after aging treatment for 1 hour and 12 hours is 54.32μm and 44.80μm respectively. The Ni 54.51 Cr 19.32 Co 16.44 Al 5.01 V 4.73 (Atomic percentage) The multi-principal alloy has an excellent match of strength and toughness after aging heat treatment. The multi-principal alloy after aging treatment for 12 hours has a yield strength of 925.5MPa, an ultimate tensile strength of 1268.6MPa, and an elongation of 24.1%. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1The X-ray diffraction pattern of the nickel-based multi-principal alloy of the present invention;
[0026] Figure 2 is a grain size distribution diagram of the nickel-based multi-principal alloy of the present invention, wherein a is a grain size distribution diagram of the alloy prepared in the comparative example, b is a grain size distribution diagram of the alloy prepared in Example 1, and c is a grain size distribution diagram of the alloy prepared in Example 2;
[0027] Figure 3 are the microstructure observation results of the nickel-based multi-principal alloy of the present invention, wherein a is the microstructure observation result of the alloy prepared in the comparative example at a scale of 100 μm, b is the microstructure observation result of the alloy prepared in the comparative example at a scale of 2 μm, c is the microstructure observation result of the alloy prepared in Example 1 at a scale of 100 μm, d is the microstructure observation result of the alloy prepared in Example 1 at a scale of 2 μm, e is the microstructure observation result of the alloy prepared in Example 2 at a scale of 100 μm, and f is the microstructure observation result of the alloy prepared in Example 2 at a scale of 2 μm;
[0028] Figure 4 It is the room temperature tensile engineering stress-strain curve of the nickel-based multi-principal alloy of the present invention. DETAILED DESCRIPTION
[0029] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0030] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0031] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0032] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0033] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0034] The present invention provides a method for preparing a high-strength and tough nickel-based multi-principal alloy, which specifically comprises the following steps:
[0035] Step 1, cleaning and proportioning of raw materials: using anhydrous ethanol and an ultrasonic cleaning machine to clean Ni, Cr, Co, Al, V metal particles with a purity of 99.99wt%, and drying for standby use, using an analytical balance with an accuracy of 0.0001g to balance the elements, the mass percentages of each element are Ni: 53-55%, Cr: 18-20%, Co: 15-17%, Al: 5-6%, V: 4-5%. Among them, the specific composition of the alloy in the embodiment and the comparative example is Ni 54.51%, Cr 19.32%, Co16.44%, Al 5.01%, V4.73% by mass percentage.
[0036] Step 2: Cleaning and degassing of vacuum arc furnace: Use anhydrous ethanol to clean the furnace cavity, and use 2000# sandpaper to polish the tungsten electrode until it is smooth. After the furnace cavity is cleaned, place the metal particle raw materials in the copper crucible in the order of melting point from low to high, and place the smooth titanium ball in the center of the crucible. Close the furnace door, and use a mechanical pump to evacuate the furnace. When the pressure in the furnace is lower than 5Pa, turn off the mechanical pump. Start the molecular pump to continue the vacuum operation. When the pressure in the furnace is lower than 1×10 - 4 Pa, it is a complete vacuum operation, and then high-purity argon is introduced into the furnace chamber to make the pressure in the furnace 0Pa. The vacuum operation is repeated 3 times to complete the gas washing. After the gas washing is completed, high-purity argon is introduced into the furnace again to make the pressure in the furnace reach -0.05MPa.
[0037] Step 3: Vacuum arc furnace smelting: First, melt the titanium ball in the center of the crucible for more than three times, observe the color change of the titanium ball after cooling, ensure that the oxygen in the furnace is exhausted, and then melt the metal particles. After the metal particles melt and cool, they form an ingot. Turn the ingot over and smelt it repeatedly for more than 8 times. At the same time, electromagnetic stirring is used to further ensure the uniformity of the alloy composition. During smelting, the current is controlled at 40-200A, and the smelting time for each time is 90-120 seconds.
[0038] Step 4, suction casting of multi-principal alloys: After smelting is completed, use the arc furnace operating rod to place the alloy ingot above the copper mold. First, heat the alloy ingot under low current conditions (150A) to make it fully and evenly heated, and then increase the current to 200A to continue heating the alloy ingot. When the ingot is about to melt into liquid, use the suction casting button to perform suction casting operation to suck the alloy into a water-cooled copper mold to obtain a multi-principal alloy block with a size of 10mm×10mm×80mm. After cooling and standing for 10 minutes, take the multi-principal alloy block out of the water-cooled copper mold.
[0039] Step 5, homogenization heat treatment: seal the multi-principal alloy block obtained by suction casting in a quartz tube, and introduce argon gas into it, and then carry out homogenization heat treatment. During the homogenization heat treatment process, set the heating rate of the Kejing KSL-1400X-A1 muffle furnace to 8°C / min, the heat treatment temperature to 1200°C, and the insulation time to 24 hours. After the insulation is completed, the multi-principal alloy is cooled to room temperature by water cooling.
[0040] Step 6, multi-pass cold rolling deformation: the multi-principal alloy after homogenization heat treatment is subjected to multi-pass cold rolling deformation, and the rolling reduction of each pass is controlled to be less than 0.5 mm, and the total rolling deformation is 80%.
[0041] Step seven, recrystallization treatment: After rolling is completed, the multi-principal alloy is subjected to recrystallization treatment. During the recrystallization treatment, the heating rate of the Kejing KSL-1400X-A1 muffle furnace is set to 8°C / minute, the recrystallization temperature is 1100°C, and the insulation time is 10 minutes. After the insulation is completed, the multi-principal alloy is water-cooled to room temperature.
[0042] Step 8, aging heat treatment: The multi-principal alloy after recrystallization treatment is subjected to aging heat treatment. During the aging heat treatment, the heating rate of the KSL-1400X-A1 muffle furnace is set to 8°C / minute. The aging heat treatment temperature is 700°C, and the holding time is set to 1 hour and 12 hours to obtain the multi-principal alloy strengthened by the L12 precipitation phase. After the holding is completed, the alloy is water-cooled to room temperature.
[0043] Example 1
[0044] This embodiment provides a method for preparing Ni 50 Cr 20 Co 15 Al 10 The method of preparing a V5 (atomic percentage) multi-principal alloy, wherein the mass percentages of the elements in the multi-principal alloy are Ni 54.51%, Cr 19.32%, Co 16.44%, Al 5.01%, and V4.73%, and the preparation process comprises the following specific steps:
[0045] (1) Raw material cleaning and proportioning: Ni, Cr, Co, Al, and V metal particles with a purity of 99.99wt.% were cleaned using anhydrous ethanol and a Shangyi ultrasonic cleaning machine, and dried for later use. The elements were weighed using a Lichen analytical balance with an accuracy of 0.0001g. The mass percentages of the elements were Ni 54.51%, Cr 19.32%, Co 16.44%, Al 5.01%, and V 4.73%, respectively.
[0046] (2) Cleaning and gas washing of vacuum arc furnace: The WK-Ⅱ vacuum arc furnace produced by Beijing Wuke Optoelectronic Technology Co., Ltd. was used for multi-principal alloy smelting. First, the furnace cavity was cleaned with anhydrous ethanol, and the tungsten electrode head was polished with 2000# sandpaper until it was smooth. After the furnace cavity was cleaned, the metal particle raw materials were placed in a copper crucible in the order of melting point from low to high, and a smooth titanium ball was placed in the center of the crucible. The furnace door was closed, and a mechanical pump was used to evacuate the furnace. When the pressure in the furnace was lower than 5 Pa, the mechanical pump was turned off and the molecular pump was started to continue the evacuation operation. When the pressure in the furnace was lower than 1×10 -4 Pa, it is a complete vacuum operation, and then high-purity argon is introduced into the furnace chamber to make the pressure in the furnace 0Pa, and the vacuum operation is repeated 3 times to complete the gas washing. After the gas washing is completed, high-purity argon is introduced into the furnace again to make the pressure in the furnace reach -0.05MPa.
[0047] (3) Vacuum arc furnace smelting: First, the titanium ball in the center of the crucible is melted more than three times, and the color change of the titanium ball after cooling is observed to ensure that the oxygen in the furnace is exhausted. Then the metal particles are melted and cooled to form an ingot. The ingot is turned over and smelted repeatedly for more than 8 times. At the same time, electromagnetic stirring is used to further ensure the uniformity of the alloy composition. The current size is controlled at 40-200A during smelting, and the smelting time for each time is 90-120 seconds.
[0048] (4) Multi-principal alloy suction casting: After smelting, the multi-principal alloy ingot is placed on the copper mold using the arc furnace operating rod. First, the alloy ingot is heated under low current conditions (150A) to ensure that it is fully and evenly heated. Then the current is increased to 200A to continue heating the alloy ingot. When the ingot is about to melt into a liquid state, the suction casting button is used to perform suction casting to suck the alloy into a water-cooled copper mold to obtain a multi-principal alloy block with a size of 10mm×10mm×80mm. After cooling and standing for 10 minutes, the multi-principal alloy block is taken out of the water-cooled copper mold.
[0049] (5) Homogenization heat treatment: The multi-principal alloy block obtained by suction casting is sealed in a quartz tube, and argon gas is introduced into it, and then homogenization heat treatment is carried out. The heating rate of the muffle furnace is set to 8°C / min, the heat treatment temperature is set to 1200°C, and the insulation time is set to 24 hours. After the insulation is completed, the multi-principal alloy is cooled to room temperature by water cooling.
[0050] (6) Multi-pass cold rolling deformation: The multi-principal alloy after homogenization heat treatment is subjected to multi-pass cold rolling deformation. During the rolling process, the rolling reduction of each pass is controlled to be less than 0.5 mm, and the total rolling deformation is 80%.
[0051] (7) Recrystallization treatment: After rolling, the multi-principal alloy was subjected to recrystallization treatment. The heating rate of the muffle furnace was set to 8°C / min to reach the target treatment temperature of 1100°C. The insulation time was 10 minutes. After the insulation was completed, the multi-principal alloy was water-cooled to room temperature.
[0052] (8) Aging heat treatment: The multi-principal alloy after recrystallization treatment is subjected to aging heat treatment to obtain a multi-principal alloy strengthened by L12 precipitation phase. The treatment temperature is 700°C and the insulation time is 1 hour. After the insulation is completed, the alloy is water-cooled to room temperature.
[0053] Example 2
[0054] The only difference between this embodiment and embodiment 1 is that the heat treatment time in step (8) is 12 hours.
[0055] Comparative Example
[0056] The only difference between this comparative example and Example 1 is that after step (7) is completed, the subsequent step (8) is not performed, and a multi-principal component alloy in a recrystallized state is obtained.
[0057] Experimental example
[0058] The above-mentioned Example 1, Example 2 and the comparative example of the present invention were tested, and the specific test methods and results are as follows:
[0059] (1) Test method
[0060] X-ray diffraction analysis: It was conducted by a Rigaku SmartLab diffractometer. The current and voltage during the test were 40kV and 150mA, respectively, and the diffraction angle (2θ) was 20°-100°. The sample size used for the test was 10mm×10mm×1.5mm. Before the test, the sample surface was polished with 400#-2000# sandpaper in sequence. The diffraction data obtained from the test was analyzed and calibrated using Jade 9 software.
[0061] Backscattered electron diffraction analysis: used to perform statistical analysis on the average grain size of the multi-principal alloy in the present invention. Backscattered electron diffraction analysis was performed using a Zeiss AurigaFocused Ion Beam scanning electron microscope equipped with an Oxford C-Swift backscattered electron diffraction signal detection collector. The collected data was analyzed using TSL OIM software. For samples used for backscattered electron diffraction analysis, the surface of the sample was first polished using 400#-2000# sandpaper in sequence, and then the surface was polished using a 50nm silica suspension to remove surface stress. The polished sample was cleaned with anhydrous ethanol for use.
[0062] Electron channel contrast imaging analysis: A Zeiss Auriga Focused Ion Beam scanning electron microscope was used to observe the microstructure of the multi-principal alloy of the present invention. The sample preparation method used for observation is the same as the sample preparation process for backscattered electron diffraction analysis.
[0063] Room temperature tensile test: The room temperature tensile test was carried out using an MTS E43.504 electronic universal testing machine, with the tensile rate set to 1×10 -4 s -1 The gauge length of the tensile test specimen is 10 mm and the width is 2 mm. The samples used for the tensile test are polished with 400#-2000# sandpaper to make the surface of the samples consistent.
[0064] (2) Test results
[0065] like Figure 1 The X-ray diffraction results of Example 1, Example 2 and the comparative example of the multi-principal alloy of the present invention are shown. It can be seen that the multi-principal alloys of Example 1, Example 2 and the comparative example are all single-phase face-centered cubic crystal structures. Considering that X-ray diffraction cannot accurately detect the precipitated phase in Example 1 and Example 2, the precipitated phase will be observed by electron channel contrast imaging analysis in the future.
[0066] like Figure 2 The grain size distribution and average grain size results of the multi-principal alloys of Example 1, Example 2 and the comparative example are shown. It can be seen that the average grain size of the multi-principal alloy of the comparative example is 62.45 μm, the average grain size of the multi-principal alloy of Example 1 is 54.32 μm, and the average grain size of the multi-principal alloy of Example 2 is 44.80 μm. It can be found that the aging heat treatment refines the grain size of the multi-principal alloy in the present invention.
[0067] Figure 3The microstructure observation results of the comparative example of the multi-principal alloy of the present invention, Example 1 and Example 2 are shown. It can be seen that the grains of the multi-principal alloy in the comparative example are equiaxed grains, and annealing twins are observed. Figure 3 The results in (b) show that there is no precipitated phase at the grain boundary. The grains of Example 1 are also equiaxed grains, in which annealing twins are also observed. Figure 3 The arrow in (d) indicates the precipitate phase formed at the grain boundary after aging treatment. The same result was observed in Example 2, and the size of the precipitate phase at the grain boundary was larger.
[0068] Figure 4 Shown are the room temperature engineering stress-strain curves of the multi-principal alloy comparative example, Example 1 and Example 2 in the present invention. It can be seen that compared with the comparative example results, the yield strength and ultimate tensile strength of Example 1 and Example 2 are significantly improved, while maintaining a good elongation. The tensile performance parameters of the comparative example, Example 1 and Example 2 are shown in Table 1. It can be seen that compared with the comparative example, the yield strength of Example 1 is increased to 676.9MPa, the ultimate tensile strength is 1090.8MPa, and the elongation is 30.8%. The yield strength and ultimate tensile strength of Example 2 are further improved, which are 925.5MPa and 1268.6MPa, respectively, while maintaining an elongation of 24.1%.
[0069] Table 1 Tensile performance parameters of the comparative example, embodiment 1 and embodiment 2 of the present invention
[0070]
[0071] Based on the above results, it can be seen that the multi-principal alloy involved in the present invention has the best strength and toughness match after aging treatment for 12 hours in the preparation process step (8), with a yield strength of 925.5 MPa, an ultimate tensile strength of 1268.6 MPa, and an elongation of 24.1%.
[0072] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A high-strength and tough nickel-based multi-principal alloy, characterized in that: The constituent elements of the high-strength and toughness nickel-based multi-principal alloy are respectively Ni: 53-55%, Cr: 18-20%, Co: 15-17%, Al: 5-6%, and V: 4-5% in mass percentage.
2. The high-strength and tough nickel-based multi-principal alloy according to claim 1, characterized in that: The components of the high-strength and tough nickel-based multi-principal alloy are Ni 54.51%, Cr 19.32%, Co 16.44%, Al 5.01%, and V 4.73% in mass percentage.
3. A method for preparing a high-strength and tough nickel-based multi-principal alloy, characterized in that: The preparation method comprises the following steps: (1) Cleaning and proportioning the raw materials according to the mass percentage of the constituent elements of the high-strength and tough nickel-based multi-principal alloy according to any one of claims 1 to 2; (2) placing the raw materials obtained in step (1) in a vacuum arc furnace for melting, and obtaining a multi-principal alloy block by suction casting; (3) The multi-principal component alloy block described in step (2) is subjected to homogenization annealing, rolling deformation and subsequent heat treatment to obtain the high-strength and toughness nickel-based multi-principal component alloy.
4. The preparation method according to claim 3, characterized in that: In step (1), the raw material is cleaned by placing Ni, Cr, Co, Al, V metal particles with a purity of 99.99wt.% in a clean beaker, ultrasonically cleaning them with anhydrous ethanol, and drying them.
5. The preparation method according to claim 3, characterized in that: In step (2), the specific steps of vacuum arc furnace smelting are: (2.1) The raw materials prepared in step (1) are placed in a copper crucible of a vacuum arc furnace in order of melting point from low to high, the furnace door is closed, and a mechanical pump and a molecular pump are used to perform vacuum treatment in sequence, so that the pressure in the furnace reaches 1×10 - 4 Pa, then high-purity argon is introduced into the furnace, and the above steps are repeated three times to exhaust all the oxygen in the furnace and obtain a clean vacuum atmosphere; (2.2) After the treatment in step (2.1), high-purity argon gas is introduced into the furnace so that the pressure in the furnace chamber is -0.05 MPa; (2.3) In the atmosphere treated in step (2.2), the cleanliness of the furnace is further checked by first melting pure titanium balls and observing the color change of their surface. During the smelting process, multiple main component alloys are smelted by controlling the current at 40-200A. After each smelting, the alloy is turned over and the smelting is repeated for more than 8 times, and electromagnetic stirring is used to further promote the uniformity of the alloy composition.
6. The preparation method according to claim 3, characterized in that: In step (2), the suction casting is to use a water-cooled copper mold to suction cast the product smelted in the vacuum arc furnace to obtain a multi-principal alloy block with a size of 10 mm×10 mm×80 mm.
7. The preparation method according to claim 3, characterized in that: In step (3), the treatment temperature during the homogenization annealing treatment is 1200° C., and the insulation time is 24 hours. After the insulation is completed, the multi-principal component alloy block is cooled to room temperature by water cooling.
8. The preparation method according to claim 3, characterized in that: In step (3), the rolling deformation is carried out by multiple cold rolling passes, with the reduction amount of each deformation not exceeding 0.5 mm, and the final rolling deformation amount is 80%.
9. The preparation method according to claim 3, characterized in that: In step (3), the subsequent heat treatment includes recrystallization annealing and aging heat treatment; the temperature of the recrystallization annealing is 1100°C, the holding time is 10 minutes, and after the holding is completed, the treatment is cooled to room temperature with water; the temperature of the aging heat treatment is 700°C, the holding time is 1-12 hours, and after the holding is completed, the treatment is cooled to room temperature with water.
10. The preparation method according to claim 9, characterized in that: The holding time during the aging heat treatment process is 12 hours.
Citation Information
Cited By
High-strength (CoCrNi) 94-xAl3Ti3Nbx multi-principal element alloy and preparation method thereof
CN121109800A
Annealing process for p-type beta-Ga2O3 film
CN121781287A